2007
DOI: 10.1021/tx060197u
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Enzyme Induction by HepG2 Cells Exposed to Oxygenated and Nonoxygenated Polycyclic Aromatic Hydrocarbons

Abstract: Oxygenated polycyclic aromatic hydrocarbons (oxy-PAHs) such as polycyclic aromatic quinones and polycyclic aromatic ketones as well as polycyclic aromatic hydrocarbons (PAHs) are abundant in the atmospheric environment. In this study, mRNA induction of six metabolic enzymes including P4501A1, 1A2, and 1B1, aldo-keto reductase 1C1 (AKR1C1), NAD(P)H-dependent quinone oxidoreductase 1 (NQO1), and glutathione S-transferase M1 (GSTM1) were examined in detail in human hepatoma (HepG2) cells exposed to environmentall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 40 publications
(78 reference statements)
4
22
0
Order By: Relevance
“…The data are expressed the means 6 S.D. causes a significant upregulation of CYP1A1/2 mRNAs expression [Misaki et al, 2007;Abdelhamid et al, 2010;Zhang et al, 2011]. Consistent with these results, DiMeDBC and mainly N-MeDBC increased substantially the CYP1A1/2 mRNA levels in HepG2 cells.…”
Section: Discussionsupporting
confidence: 82%
“…The data are expressed the means 6 S.D. causes a significant upregulation of CYP1A1/2 mRNAs expression [Misaki et al, 2007;Abdelhamid et al, 2010;Zhang et al, 2011]. Consistent with these results, DiMeDBC and mainly N-MeDBC increased substantially the CYP1A1/2 mRNA levels in HepG2 cells.…”
Section: Discussionsupporting
confidence: 82%
“…Induction equivalency factor (IEF) is the ratio of EC TCDD25 of test compound relative to benzo[ a ]pyrene (B[ a ]P). Data regarding CYP1A1 mRNA induction are from Misaki et al [25]. PhO = phenalenone; BAO = 7 H ‐benz[ de ]anthracen‐7‐one; FlO = fluorenone; AO = anthrone; XO = xanthone; TXO = thioxanthone; B[ a ]FO = 11 H ‐benzo[ a ]fluoren‐11‐one; B[ a ]FO = 11 H ‐benzo[ b ]fluoren‐11‐one; B[ c ]FO = 7 H ‐benzo[ c ]fluoren‐7‐one; CPPO = cyclopenta[ cd ]pyren‐3[4 H ]‐one; BPO = 6 H ‐benzo[ de ]pyren‐6‐one; AQ = anthraquinone; PhQ = phenanthrenequinone; ChQ = 1,4‐chrysenequinone; BAQ = 7,12‐benz[ a ]anthracenequinone; NCQ = 5,12‐naphthacenequinone; Alz = alizarin; PCQ = pentacenequinone; NA = 1,8‐naphthalic anhydride; β‐NF = β‐naphthoflavone; Nph = naphthalene; ANthyl = acenaphthylene; ANthe = acenaphthene; Fl = fluorene; Ant = anthracene; Ph = phenanthrene; FA = fluoranthene; Py = pyrene; B[ a ]A = benz[ a ]anthracene; Chr = chrysene; TPh = triphenylene; B[ b ]F = benzo[ b ]fluorene; B[ b ]FA = benzo[ b ]fluoranthene; B[ k ]FA = benzo[ k ]fluoranthene; B[ a ]P = benzo[ a ]pyrene; DB[ a,h ]A = dibenz[ a,h ]anthracene; DB[ a,c ]A = dibenz[ a,c ]anthracene; 3‐MC = 3‐methylcholanthrene; IdP = indeno[1,2,3‐ cd ]pyrene; B[ ghi ]Pe = benzo[ ghi ]perylene; N[ a ]P = naphtho[2,3‐ a ]pyrene; U = <25% of TCDD max; NI = not induced.…”
Section: Resultsmentioning
confidence: 99%
“…16) It has been reported that oxygenated PAHs which are polar compounds contribute more greatly than PAHs to the AhR activity of environmental air samples. 17,18) PAH ketones and quinones originating from gasoline and diesel engine exhausts are present at comparatively high concentrations (e.g., 11H-benzo[a]fluoren-11-one: 1.026 ± 0.037 ng/m 3 , 5) comparing with other detected compounds, and 9,10-PQ also exist at high concentration in ambient air. 6) The high concentration of PAH ketones and quinones in the atmosphere suggest that large amount of human exposure to these compounds through respiration.…”
Section: Discussionmentioning
confidence: 99%